Development and testing of an aerosol/stratus cloud parameterization scheme for middle and high latitudes. Year 3 technical progress report, November 1, 1996--August 31, 1997 - Kreidenweis, S.M.; Cotton, W.R. (Colorado State University. Department of Atmospheric Science., 1997)
At the present time, general circulation models (GCMs) poorly represent clouds, to the extent that they cannot be relied upon to simulate the climatic effects of increasing concentrations of greenhouse gases, or of anthropogenic perturbations to concentrations of cloud condensation nuclei (CCN) or ice nuclei (IN). The net radiative forcing of clouds varies strongly with latitude. Poleward of 30 degrees in both hemispheres, low-level clouds create a net cooling effect corresponding to radiative divergences of {minus}50 to {minus}100 W/msup 2. It is likely that a combination of fogs, boundary-layer stratocumulus, and stratus clouds are the main contributors to this forcing. Models of the response of the microphysical and radiative properties of clouds to changes in aerosol abundance, for a variety of large-scale meteorological forcings, are important additions to GCMs used for the study of the role of Arctic systems in global climate. The overall objective of this research is the development of an aerosol/cloud microphysics parameterization of mixed-phase stratus and boundary-layer clouds which responds to variations in CCN and IN. The parameterization is to be designed for ultimate use in GCM simulations as a tool in understanding the role of CCN, IN, and Arctic clouds in radiation budgets. Several versions of the CSU RAMS (Regional Atmospheric Modeling System) will be used during the course of this work. The parameterizations developed in this research are intended for application in a single-column cloud model, designed as an adaptive grid model which can interface into a GCM vertical grid through distinct layers of the troposphere where the presence of layer clouds is expected.